Differential diagnosis of clear cell renal cell carcinoma with low signal intensity on T2WI from angiomyolipoma without visible fat on MR imaging - Chen, Zi-xuan; Zhang, Yi; Ren, Shuai; Cao, Ying-ying; Lan, Qi; Xia, Fan; Wang, Zhong-qiu; Qiu, Wen-li (Frontiers in Oncology, 2025)
PurposeThis study aimed to determine the potential of magnetic resonance imaging (MRI) parameters in differentiating between angiomyolipoma without visible fat (AML.wovf) and clear cell renal cell carcinoma (ccRCC) with low signal intensity on T2-weighted imaging (T2WI).Materials and methodsThis is a retrospective study involving 36 cases of ccRCC and 17 cases of AML.wovf from September 2016 to July 2023. All patients underwent histological examination on resected specimens and contrast-enhanced magnetic resonance imaging (CE-MRI). Clinical characteristics such as age, gender, and symptoms of hematuria and lumbago were recorded. A panel of MRI parameters were analyzed, including the tumor growth patterns, the wedge-shaped sign, pseudocapsule formation, the arterial-to-delayed enhancement ratio (ADER), and the apparent diffusion coefficient (ADC). The potential of these MRI parameters in distinguishing ccRCC from AML.wovf was finally determined and visualized in a nomogram.ResultsThere were no significant differences in age, gender, and clinical symptoms between the ccRCC and AML.wovf groups. The wedge-shaped sign was more prevalent in patients with AML.wovf (p = 0.027), while pseudocapsule formation was mainly observed in cases of ccRCC (p < 0.001). Quantitative MRI revealed a significantly lower ADC in patients with AML.wovf (p = 0.007). Pseudocapsule formation (OR = 140.29, p = 0.004), the wedge-shaped sign (OR = 0.05, p = 0.047), and ADC (OR = 36.22, p = 0.037) were independent predictors for differentiating between AML.wovf and ccRCC, and their combination demonstrated the highest diagnostic accuracy, with an area under the curve (AUC) of 0.913 in the receiver operating characteristic (ROC) analysis.ConclusionA combination of MRI parameters, including the wedge-shaped sign, pseudocapsule formation, and ADC, can accurately differentiate between AML.wovf and ccRCC.